Een vertekend beeld? Opnieuw de toeschrijving van de dolhuisvrouw (Bulletin KNOB, 2017)
Who created the Dolhuisvrouw (Madhouse Woman) and when? The debate surrounding these questions can be traced back to two art historians, Elisabeth Neurdenburg and Juliane Gabriels. This article provides a response to Frits Scholten’s article on the subject in Bulletin KNOB no. 1, 2017, a few additions to my own article in Bulletin KNOB no. 2, 2016, and a conclusion about the art-historical context of the attribution of the Dolhuisvrouw. Scholten, who is in agreement with Gabriels’ 1930 monograph, Artus Quellien, de Oude ‘Kunstryck belthouwer’, quotes part of her argumentation and fully endorses her attribution of the Dolhuisvrouw to Artus Quellinus. However, Scholten fails to mention a crucial footnote in a later article by Neurdenburg in the 1943 Oudheidkundig Jaarboek, in which Gabriels declares that she now supports the statue’s attribution to Hendrick de Keyser. Various earlier authors have linked the appearance of the Dolhuisvrouw to a renovation in 1615, and thus to the working life of Hendrick de Keyser. Such an early date seems unlikely because the Dolhuisvrouw is absent from a meticulous map drawn in 1625 by Balthasar Floris, which shows the divided courtyard minus the statue. In the context of this debate, it is important to consider the work of Gerrit Lambertsen, Hendrick de Keyser’s pupil. Apart from a test piece in wood, Lambertsen worked exclusively in sandstone, without signing his work. Although the Dolhuisvrouw has a smooth finish, the plinth exhibits the typical input of a stone mason – of someone who is familiar with sandstone. A reference to styles proves to be of little direct use in arriving at a more accurate dating of the Dolhuisvrouw. Nowadays there are better arguments for dating the statue to the first half of the seventeenth century. Owing to a Calvinist prohibition on licentious nudity, it is likely that the statue initially stood indoors, but historical clues have been discovered that for the time being support Gerrit Lambertsen’s authorship in the second quarter of the century. For an older generation of art historians, form was all-decisive and some did not even mention material and finish. The great masters of the seventeenth century did indeed work in various materials or sought out other specialists to have their works realized in bronze or terracotta. Hendrik de Keyser and his pupil Gerrit Lambertsen both had their own workshops at different points in time, but had a lot in common in terms of origins, style and technique. This was acknowledged by Neurdenburg, as was the comparable relationship between the younger baroque sculptors from the southern Netherlands, Artus Quellinus and Rombout Verhulst. As in painting, older generations of art historians carried out pioneering work, but they looked for ‘geniuses’ in a much too small pool of talent. With selective quotations and attributions Scholten is himself continuing to contribute to what he calls ‘a stubborn misunderstanding’ requiring correction and qualification.